Pengaruh Informasi Akuntansi Manajemen terhadap Fungsi Manajemen, Kebijakan Produksi, dan Kinerja Proses Bisnis Internal - Rusliati, Ellen (Jurnal Trikonomika, 2009)
Manufacturing companies listed at the Indonesian Stock Exchange both resulting ROI and ROE on average are more less than mean interest rate. Companies with differentiation strategy are more than cost leadership. Management accounting information available is function based, the implementation of management function was effective and production policy implementation was fair, and internal business performance was moderate. Using management accounting information has an effect directly on internal business process performance and indirectly by the effectiveness of management function and production policy implementation, in manufacturing companies with differentiation strategy. In manufacturing companies with cost leadership strategy, using of management accounting information has an effect directly on the effectiveness of management function implementation and effectiveness of management function implementation has an effect directly on production policy implementation.